Psychological Well Being of School Counselors - Mahomed, Nur Jannah Bali; Johari, Ku Suhaila Ku; Mahmud, 3Mohd Izwan (International Journal of Psychosocial Rehabilitation, 2020)
ABSTRACT— National development and government initiatives in realizing educational transformation has made the profession of school counsellors facing a challenging and vulnerable role with stress that affects their well-being. Aspects of psychological well-being of school counsellors need to be explored and understood to ensure their services in schools are implemented effectively. The study aims to understand contribution of self-compassion to psychological well-being among school counsellors. The results of the previous studies have found that; (i) self- compassion contribute to the psychological well-being of school counsellors; and (ii) good psychological well- being of teachers can improve the quality of counselling services. The implication of this study explains the need to improve psychological well-being among school counsellors. Proposed follow-up recommendations need to be done by focusing on quantitative studies aimed at better understanding of this issue.